2020
DOI: 10.1186/s12884-020-2833-2
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for previous Cesarean deliveries impact a woman’s independent decision of delivery mode and the success of trial of labor after Cesarean

Abstract: Background: Cesarean delivery rates are increasing globally with almost half of them occurring due to a previous Cesarean delivery. A trial of labor after Cesarean (TOLAC) is considered a safe procedure, but most eligible women instead undergo Cesarean before 39 weeks of gestation. Lack of education about TOLAC is often associated with increased repeat Cesarean. To reveal the safety and feasibility of TOLAC, we conducted this observational, prospective study with women's independent decisions. We aimed to clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 33 publications
1
29
1
Order By: Relevance
“…Repeat CS is not indicated for all women with previous CS in the subsequent pregnancies and vaginal birth after CS (VBAC) can be encouraged, especially in centers equipped with obstetricians. Studies in some countries have shown that VBAC has a success rate of 91.3%, 15 especially in women who underwent vaginal birth before CS and for whom fetal malpresentation was the indications for a previous CS. Usually VBAC is associated with lower morbidity compared with repeat CS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeat CS is not indicated for all women with previous CS in the subsequent pregnancies and vaginal birth after CS (VBAC) can be encouraged, especially in centers equipped with obstetricians. Studies in some countries have shown that VBAC has a success rate of 91.3%, 15 especially in women who underwent vaginal birth before CS and for whom fetal malpresentation was the indications for a previous CS. Usually VBAC is associated with lower morbidity compared with repeat CS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in some countries have shown that VBAC has a success rate of 91.3%,15 especially in women who underwent vaginal birth before CS and for whom fetal malpresentation was the indications for a previous CS. Usually VBAC is associated with lower morbidity compared with repeat CS.…”
mentioning
confidence: 99%
“…The proposed rates of successful VBAC have been reported to be 60-80% [9,10,11]. However, the VBAC success rate is lower in Africa including Ethiopia [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the VBAC success rate is lower in Africa including Ethiopia [12,13,14]. For example successful VBAC was 48% in Nigeria [12], 48% in Ghana [14], and 45.5% in Ethiopia [13] Although successful VBAC is a safer and a more recommended method for women with previous single caesarean section delivery than undergoing elective repeat caesarean delivery [15], the chance of successful VBAC is determined by factors such as history of previous vaginal delivery, cervical dilatation and station at admission, birth weight >4 kg, cephalo-pelvic disproportion, and maternal age [8,15]; Studies revealed that previous history of vaginal delivery is the best predictor of VBAC success [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…According to an analysis on the ways and outcomes of childbirth in Asia published in 2010 (7), cesarean delivery increases the risk of maternal death, admission to the ICU, blood transfusion, hysterectomy, and iliac artery ligation. Pregnant women with a history of cesarean delivery, irrespective of whether they choose a cesarean or vaginal delivery at the present, are at a higher risk of developing complications than those who had a normal vaginal delivery the first time, including serious adverse events such as uterine rupture and maternal and neonatal death (8,9). Complications related to the placenta are among the more serious consequences of previous CS (10).…”
Section: Principal Findings Of the Studymentioning
confidence: 99%